SOCIAL NETWORKING WEB APPLICATION USING STRUTS FRAMEWORK. - Maharjan, Saroj (InSight: Rivier Academic Journal)
There are a number of framework technologies which can be used to develop web applications. But since the web applications are getting more complex over time, the frameworks that can used to develop them should also be advanced to handle the complex requirements. This project walks us thorough Struts framework, which is one of most popular and used web application frameworks. The project was part of the final project implemented for CS699 "Professional Seminar in Computer Science" course which is based on the research on Struts framework and a web application which was developed based on Struts. This article summaries the benefits of using Struts framework in web application, its comparison with LAMP technology, drawbacks of Struts and finally, the web application which was developed following the software development steps.